Methicillin Resistant Staphylococcus Aureus in patients visiting Western Regional Hospital, Pokhara - Rijal, KR; Shrestha, N; Pahari, N; Shrestha, B; Paudel, B; Nepal, A; Ghimire, P; Rijal, B (Journal of Institute of Medicine Nepal, 2008)
<!–[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if !mso]> <![endif]–> <!–[if gte mso 10]> <![endif]–> Introduction: Methicillin Resistant Staphylococcus aureus (MRSA) continues to be a major cause of serious infection in hospitals and in the community worldwide. This study was performed to determine the prevalence of Methicillin resistant Staphylococcus aureus in healthy school children and patients visiting Western Regional Hospital of Pokhara. Methods: The children from three Schools namely Janapirya Higher Secondary School, Sublime School and Ratnajyoti School and patients visiting Western Regional Hospital were selected for the study. This study was conducted by The School of Pharmaceutical and Biomedical Sciences during July to November 2007. One hundred eighty four Nasal swabs were collected from the healthy school children younger than 15 years old and one hundred clinical samples such as pus, wound swabs were collected from patients attending Western Regional Hospital. Collected nasal swabs and clinical swabs were analyzed for the growth of Staphylococcus aureus on mannitol salt agar (MSA). S. aureus was isolated and identified by mannitol fermentation, coagulase positivity and DNase positivity. Antimicrobial susceptibility test was performed on Muller-Hinton agar (MHA) medium by Modified Kirby-Bauer disc diffusion method. Results: Out of 284 samples, 184 were nasal swabs, from healthy school children and 100 were clinical samples from patients attending Western Regional Hospital. Out of total nasal swabs (n=184), S. aureus was isolated from 30.97 % (n=57). Out of 57 isolates of Staphylococcus aureus, isolated from healthy school children 56.14 % (n=32) were MRSA. Out of 100 clinical samples isolated from hospital patients, S. aureus was isolated from 45% (n= 45).Out of 45 isolates of S. aureus, 75.55% (n=34) were MRSA. Prevalence of MRSA was statistically significant in clinical specimens in comparison with nasal swabs isolated from healthy school children (P < 0.05). Conclusion: This study showed a high prevalence of MRSA carriage in school children and hospital patients of Pokhara valley and this may indicate the spread of MRSA in the community. Larger community based studies and regular surveillance of MRSA are needed to assist in the development of therapeutic guidelines for MRSA. Key words: Staphylococcus aureus, MRSA, MHA, Modified Kirby-Bauer method Journal of Institute of Medicine, April, 2008; 30:1 21-25 The full text of this paper is available from the Journal of Institute of Medicine website